Auditory Displays for Take-Over in Semi-automated Vehicles - Richie, Erin; Offer-Westort, Thomas; Shankar, Raghavendran; Jeon, Myounghoon (Digital Human Modeling. Applications in Health, Safety, Ergonomics, and Risk Management, 2018)
With the field of automated vehicles rapidly growing comes the question of how we communicate to a driver that they need to take over in emergency or other urgent situations. Auditory displays can enhance communications between the driver and the automated vehicle. After a review of related literature, guidelines for audio displays were determined and a preliminary pilot experiment was conducted to further understand how drivers’ reaction time to urgent situations would vary based on the type of sound they were alerted with. Results suggest that speech may give the quickest response time and a word choice may matter if using a spearcon. This paper is expected to contribute to designing further research studies for take-over displays in the automated vehicle.